E-Book Design Analysis: The Effectiveness of Interactive Media in Understanding Characters and Ethnoscience Concepts - Dede Latipah; Dewiantika Azizah; Mochamad Arief Mardiansah; Lucky Dewianti; Ade Tio Sopian (Politeknik Ganesha Medan, 2026)
This research aims to develop a contextual-based interactive e-book integrating West Javanese folktales and ethnoscience concepts to enhance students’ understanding of natural phenomena in second-grade science at SDIT Abdurrahman Bin Arif, Curug, Bogor City. The study employed the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation stages. Data were obtained through expert validation, individual and small group testing, and effectiveness testing using pre-test and post-test instruments. Validation was conducted by media, language, and ethnoscience experts. The trial was performed on 29 second-grade students. The results showed excellent feasibility with expert assessments reaching over 90% in each category. The t-test analysis revealed a significant improvement in students’ learning outcomes after using the e-book (sig. 0.000 < 0.05). This indicates that the e-book was effective in increasing students' conceptual understanding of environmental changes through the integration of cultural narratives. The use of contextual e-books not only supports meaningful learning but also promotes character values such as responsibility and environmental awareness. Thus, the developed e-book is considered valid, practical, and effective for science learning in primary education